How Shortening the Potential Duration of Unemployment Benefits Affects the Duration of Unemployment: Evidence from a Natural Experiment - van Ours, Jan C.; Vodopivec, Milan (Journal of Labor Economics, 2006)
In this article we investigate the disincentive effects of shortening the potential duration of unemployment insurance (UI) benefits. We identify these disincentive effects by exploiting changes in Slovenia’s unemployment insurance system—a “natural experiment” that involved substantial reductions in the potential duration of benefits for four groups of workers plus no change in benefits for another group (which served as a natural control). We find that the change had a positive effect on the exit rate from unemployment—to new jobs and other options—for unemployment spells of various lengths and for several categories of unemployed workers.